2022
DOI: 10.1108/jfm-12-2021-0162
|View full text |Cite
|
Sign up to set email alerts
|

The effect of COVID-19 on Indian stock market volatility: can economic package control the uncertainty?

Abstract: Purpose The stock market has shown fluctuating degrees of volatility because of the recent COVID-19 pandemic in India. The present research aims to investigate the effect of the COVID-19 on the stock market volatility, and whether the economic package can control the market volatility or not, measured by a set of certain sector-level economic features and factors such as resilience variables. Design/methodology/approach We examine the correlation matrix, basic volatility model and robustness tests to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
(39 reference statements)
0
8
0
Order By: Relevance
“…There has been a sudden spurt of academic studies cutting across various domains of knowledge on the factors contributing to the increase of COVID-19 pandemic cases, transmissions and deaths. These studies mainly focus on the following: spatial effects of COVID-19 (Guliyev 2020); effects on temperature and humidity variations in the number of COVID-19 deaths (Ma et al 2020;Wu et al 2020;Qi et al 2020); environmental impacts on COVID-19 transmission (Xu et al 2020); air pollution and COVID-19 infection (Yongjian et al 2020;Bontempi 2020); maternal deaths due to COVID-19 (Hantoushzadeh et al 2020); association between the COVID-19 cases and deaths (Sarkodie and Owusu 2020); COVID-19 and stock market volatility (Sreenu and Pradhan 2022); COVID-19 and microfinance institutions (Sangwan et al 2021); social distancing and COVID-19 death (Conyon et al 2020); labour mobility and fatality due to COVID-19 (Wright et al 2020); nationalism and COVID-19 (Wang 2021;Gülseven 2021;Zhao 2021;Pan and Korolev 2021;Lin 2021;Givens and Mistur 2021;Yang and Chen 2021;Zhao 2021;Boylan et al 2021;Albertoni and Wise 2021;He and Chen 2021); global politics and COVID-19 (Salvati 2021;Makarychev and Romashko 2021;Chen 2021; Wang and Sun 2021;Lin 2021;Huang 2021;Chang 2021;Jaworsky and Qiaoan 2021;Caballero-Anthony and Gong 2021); mitigating measures against COVID-19 (Zhang et al 2021;Ullah et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…There has been a sudden spurt of academic studies cutting across various domains of knowledge on the factors contributing to the increase of COVID-19 pandemic cases, transmissions and deaths. These studies mainly focus on the following: spatial effects of COVID-19 (Guliyev 2020); effects on temperature and humidity variations in the number of COVID-19 deaths (Ma et al 2020;Wu et al 2020;Qi et al 2020); environmental impacts on COVID-19 transmission (Xu et al 2020); air pollution and COVID-19 infection (Yongjian et al 2020;Bontempi 2020); maternal deaths due to COVID-19 (Hantoushzadeh et al 2020); association between the COVID-19 cases and deaths (Sarkodie and Owusu 2020); COVID-19 and stock market volatility (Sreenu and Pradhan 2022); COVID-19 and microfinance institutions (Sangwan et al 2021); social distancing and COVID-19 death (Conyon et al 2020); labour mobility and fatality due to COVID-19 (Wright et al 2020); nationalism and COVID-19 (Wang 2021;Gülseven 2021;Zhao 2021;Pan and Korolev 2021;Lin 2021;Givens and Mistur 2021;Yang and Chen 2021;Zhao 2021;Boylan et al 2021;Albertoni and Wise 2021;He and Chen 2021); global politics and COVID-19 (Salvati 2021;Makarychev and Romashko 2021;Chen 2021; Wang and Sun 2021;Lin 2021;Huang 2021;Chang 2021;Jaworsky and Qiaoan 2021;Caballero-Anthony and Gong 2021); mitigating measures against COVID-19 (Zhang et al 2021;Ullah et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…According to the Indian channel reports, the NSE Nifty 50 and BSE Sensex 30 industrial averages had declined by more than 35% and 48%, respectively. This was the largest quarterly decline in share value since 1937 (Sreenu and Pradhan, 2022).…”
Section: Discussion and Analysismentioning
confidence: 99%
“…These studies mostly focussed on developed markets, especially the US, UK and China (Fama and Eugene 1990; Comincioli, 1996; Han et al. , 2015) amongst others, confirmed the stock market’s role as a leading indicator of economic activity (Javaira and Hassan, 2015; Sreenu and Pradhan, 2022) said that stock prices are no longer a leading indicator of economic activity in the developing countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Liu et al (2019) found evidence in the published research that the COVID-19 outbreak had a negative impact on the performance of stock markets in a variety of countries, including Korea, Japan, the United States, Germany, the United Kingdom and others. Sreenu and Pradhan (2022) and, Humpe and McMillan (2020); discovered that verified cases of COVID-19 had an immediate and detrimental impact on the stock markets. According to the findings of (Humpe and McMillan, 2020), the daily increase in the number of confirmed cases and deaths had a significant and detrimental impact on the stock returns of all companies trading on the US stock market.…”
Section: Structural Break and Stock Pricesmentioning
confidence: 99%